2021
DOI: 10.5312/wjo.v12.i4.223
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of clinical outcomes after non-operative management of symptomatic full-thickness rotator cuff tears

Abstract: BACKGROUND Previous studies have shown that non-surgical management can be an effective treatment strategy for many patients with rotator cuff tears. Despite the prevalence of rotator cuff disease, few studies have examined the patient and tear related factors that predict outcomes of nonsurgical management in this cohort of patients. AIM To identify factors that are associated with changes in patient reported outcomes over time in individuals with full-thickness rotato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…We excluded two recent studies including patients with revision repairs or nonoperative treatment. 5 , 24 Screening of the titles and abstracts of cited and citing references of included records and 18 topical records 7 , 8 , 9 , 15 , 23 , 24 , 26 , 30 , 35 , 40 , 42 , 55 , 58 , 60 , 70 , 71 , 72 , 73 did not yield any additional studies that met our inclusion criteria. A full description of included studies (studied population, outcomes, statistical analyses, and reported effect estimates) is available in Supplemental Tables 1-3 .…”
Section: Resultsmentioning
confidence: 99%
“…We excluded two recent studies including patients with revision repairs or nonoperative treatment. 5 , 24 Screening of the titles and abstracts of cited and citing references of included records and 18 topical records 7 , 8 , 9 , 15 , 23 , 24 , 26 , 30 , 35 , 40 , 42 , 55 , 58 , 60 , 70 , 71 , 72 , 73 did not yield any additional studies that met our inclusion criteria. A full description of included studies (studied population, outcomes, statistical analyses, and reported effect estimates) is available in Supplemental Tables 1-3 .…”
Section: Resultsmentioning
confidence: 99%